O maternar enlutado: as memórias de uma mãe nos processos de luto e autoconhecimento - Mazzoni, Marcela Fabiana Rodgher (Universidade Federal de São Carlos, 2024)
Pregnancy includes several transformations, both physical and emotional, including changes in hormones and variations in self-esteem. Neonatal loss constitutes a challenge and is a relevant public health indicator. To promote adequate care for mothers and considering that this loss is one of the most complex daily griefs and has impacts on occupations, identity and social participation, it is necessary to study it. Thus, support groups emerge as a welcoming space and provide a better quality of life for bereaved mothers, enabling the expression of feelings and a sense of belonging. Objective: The objective was to understand the mothering experience in the processes of grief and self-knowledge, and to describe the participation of a bereaved mother in a support group for neonatal loss. Materials and Methods: This is a qualitative research, with a case study design, using semi-structured interviews to obtain personal information, the grieving process, before and after the loss and participation in a support group, and the Timeline as an instrument for recording important dates related to participation in the group. Results: Three categories emerged that addressed the impacts on daily life, routine and obstacles in the life of the bereaved mother, the lack of immediate recognition of the maternal occupational identity and the effects of participating in a support group. Conclusion: It is concluded that the mother's strategies, such as the gradual return to activities and her support network to deal with the changes of pregnancy and loss, were essential for her recovery. Furthermore, the construction and recognition of maternal identity, along with changes in daily activities, require time, reframing and support. Participation in a support group also had positive impacts on mourning, adapting to a new routine and facing everyday challenges.
Bereaved mothering: a mother's memories in the processes of bereavement and self-knowledge
Keywords: Morte perinatal; Luto; Grupos de apoio; Maternidade; Ocupações; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL